2015
DOI: 10.1021/acs.jnatprod.5b00415
|View full text |Cite
|
Sign up to set email alerts
|

Acetate-Derived Metabolites from the Brown Alga Lobophora variegata

Abstract: Seven new nonadecaketides (1-7), lobophorols A-C, lobophopyranones A and B, and lobophorones A and B, along with the first naturally occurring related metabolites (8-10), were isolated from specimens of Lobophora variegata collected from the Canary Islands. Their structures were determined by extensive spectroscopic methods. In addition, an insight into the biosynthesis of these compounds on the basis of the involvement of type III polyketide synthases is proposed. Lobophorol A (1) showed significant antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 29 publications
(51 reference statements)
2
27
0
Order By: Relevance
“…This was suggested to be due to an increase in alkene production during rapid growth of the alga or potentially due to smaller alkene losses in the Southern hemisphere winter [79]. The brown alga Lobophora variegata, commonly found in the Canary Islands, was also shown to yield saturated and unsaturated ketones (225-227) [80]. This particular species of algae has been reported to suffer extremely low levels of microbial infection and has also been studied in an ecological perspective with particular interest in its role in absorbing heavy metal ions [81].…”
Section: Lipidsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was suggested to be due to an increase in alkene production during rapid growth of the alga or potentially due to smaller alkene losses in the Southern hemisphere winter [79]. The brown alga Lobophora variegata, commonly found in the Canary Islands, was also shown to yield saturated and unsaturated ketones (225-227) [80]. This particular species of algae has been reported to suffer extremely low levels of microbial infection and has also been studied in an ecological perspective with particular interest in its role in absorbing heavy metal ions [81].…”
Section: Lipidsmentioning
confidence: 99%
“…This particular species of algae has been reported to suffer extremely low levels of microbial infection and has also been studied in an ecological perspective with particular interest in its role in absorbing heavy metal ions [81]. A 2015 study examined the anti-bacterial properties of the compound lobophorone E (227) against both Gram-negative and Gram-positive bacteria, but it was shown to be significantly outperformed by the positive control ciprofloxacin [80].…”
Section: Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three sulfoquinovosyldiacylglycerols (SQDGs) and later lobophorolide were identified from L. variegate (Cantillo-Ciau et al, 2010;Kubanek et al, 2003). Recently, seven nonadecaketides named lobophorols, lobophopyranones and lobophorones (Gutiérrez-Cepeda et al, 2015) were found in the Atlantic L. variegate while the polyunsaturated lobophorenols A, B and C were described in the tropical L. rosacea (Vieira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%